The Rise of Groundwater Due to Rainfall and the Control of Landslide by Zero-Energy Groundwater Withdrawal System - Alsubal, Shamsan; Sapari, Nasiman; S.H. Harahap, Indra (International Journal of Engineering and Technology, 2018)
Slope failure is a common issue in tropical countries. The rise of groundwater table due to rainfall is one of the main triggering factors. There are several methods for slope stabilization such as soil nailing, retaining walls, cut and fill, vegetation and so on. Most of those methods are costly and we are in need for stabilizing methods that are more economical and easier to construct. This article introduces a new method for slope stability. This method is examined numerically and experimentally. It is represented in an automatic zero-energy groundwater withdrawal system to enhance slope stability. The system is validated in a pre-fabricated model to ensure that it works on natural soil slope. The numerical simulation is performed in Soilworks software with coupled seepage-slope stability analysis using finite element methods to check the safety factor with and without the system. The effectiveness of this method is investigated with various rainfall intensities and soil permeabilities. The results for slopes with the application of groundwater withdrawal system are compared with the results without the system. The results demonstrate the effectiveness of the proposed method in reducing groundwater table and enhancing slope stability. The factor of safety for the slope with high soil permeability drops from 1.312 before the rainfall to 1.292 and 0.93 after the third rainfall event for the slope with and without pumping groundwater respectively. For soil slope with moderate soil permeability, the factor of safety deteriorates from 1.314 to 1.157 at the end of the third day, while it remains stable with pumping groundwater. Matric suction is highly increased at the crest of the slope due to pumping.Â